1998
DOI: 10.1016/s1097-2765(00)80123-9
|View full text |Cite
|
Sign up to set email alerts
|

Function of Hexameric RNA in Packaging of Bacteriophage φ29 DNA In Vitro

Abstract: A cyclic hexamer of the 120-base prohead RNA (pRNA) is needed for efficient in vitro packaging of the B. subtilis bacteriophage phi 29 genome. This capacity of pRNA to form higher multimers by intermolecular base pairing of identical subunits represents a new RNA structural motif. Dimers of pRNA are likely intermediates in formation of the cyclic hexamer. A three-dimensional model of the pRNA hexamer is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
207
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(216 citation statements)
references
References 24 publications
4
207
5
Order By: Relevance
“…The ϕ29 connector, a cone-shaped dodecamer of gene product 10 (gp10), occupies the pentagonal vertex at the base of the prohead 5 and is the portal for DNA entry during packaging and DNA ejection during infection 6 . The connector, in association with the oligomeric, ϕ29-encoded prohead RNA (pRNA) and a viral ATPase (gp16), is required for DNA packaging [7][8][9] . However, only the first 120 bases of the 174-base pRNA are essential for packaging 7 the genomic dsDNA with gp3 (DNA-gp3) can be packaged into proheads in about three minutes in vitro (P.J.J., unpublished results).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The ϕ29 connector, a cone-shaped dodecamer of gene product 10 (gp10), occupies the pentagonal vertex at the base of the prohead 5 and is the portal for DNA entry during packaging and DNA ejection during infection 6 . The connector, in association with the oligomeric, ϕ29-encoded prohead RNA (pRNA) and a viral ATPase (gp16), is required for DNA packaging [7][8][9] . However, only the first 120 bases of the 174-base pRNA are essential for packaging 7 the genomic dsDNA with gp3 (DNA-gp3) can be packaged into proheads in about three minutes in vitro (P.J.J., unpublished results).…”
mentioning
confidence: 99%
“…1d) was based on reconstructions in which the five-fold symmetry had been imposed along the long axis of the particles. If the pRNA were six-fold symmetric as suggested by genetic data 8,9 , the resultant averaged density would be weak and smeared. However, we observe that the pRNA has excellent density, higher by a factor of ~1.5 than the density of the head, thus demonstrating that the pRNA is consistent with the imposed five-fold symmetry.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1B), with the remaining 39-nt P A helix providing the binding site for the gp16 ATPase (3,12). Early studies demonstrated that pRNA oligomerization is mediated by an intermolecular pseudoknot formed by base-pairing between an internal loop L CE in one pRNA and the L D loop of another pRNA (13,14).…”
mentioning
confidence: 99%